Odpowiedzi

2010-02-26T10:51:35+01:00
A) 5x+10y=5(x+2y)
b) 4m+4=4(m+1)
c) 3a-3=3(a-1)
d) 5xy-x=x(5y-1)
e) 6a²-2a=2a(3a-1)
f) 6a²-12ab=6a(a-2b)
g) 1/2xy-1/2x=1/2x(y-1)
h) 1/3a²b+1/9ab²=1/3ab(a+1/3b)
i) 2xyz-4x²y²z+xyz²=xyz(2-4xy+z)
j) stv²-stv+tv²=tv(sv-s+v)
1 5 1
2010-02-26T10:52:26+01:00
A) 5x+10y = 5(x+2y)
b) 4m+4 = 4(m+1)
c) 3a-3 = 3(a-1)
d) 5xy-x = x(5y-1)
e) 6a²-2a = 2a(3a-1)
f) 6a²-12ab = 6a(a-12b)
g) 1/2xy-1/2x = 1/2x(y-1)
h) 1/3a²b+1/9ab² = 1/3ab(a+1/3b)
i) 2xyz-4x²y²z+xyz² = xyz(2-4xy+z)
j) stv²-stv+tv² = tv(sv-s+v)
1 5 1
2010-02-26T10:52:27+01:00
A) 5x+10y=5(x+2y)
b) 4m+4=4(m+1)
c) 3a-3= 3(a-1)
d) 5xy-x=x(5y-1)
e) 6a²-2a=2a(3a-1)
f) 6a²-12ab=6a(a-2b)
g) 1/2xy-1/2x=1/2x(y-1)
h) 1/3a²b+1/9ab²=1/3ab(a+1/3b)
i) 2xyz-4x²y²z+xyz²=xyz(2-4xy+z)
j) stv²-stv+tv²=tv(sv-s+v)
1 5 1